Computation of solar radiation heat gain in analysing energy efficient operation of an air-conditioning system - Syahrul Ramadhan, Ahmad Kamal Ariffin (2013)
In any building, air-conditioning system is essential to maintain thermal comfort of the occupants as well as ensuring their optimum productivity. However, the electricityconsumption by air conditioning alone is more than 50% from the total electricityconsumption. Hence it must be designed carefully to optimize electrical energy suppliedand avoid energy wastage. The operation of an air-conditioning system are dependlargely on the heat gain absorbed by the building. Heat gain may come from internal heat gain as well as external heat gain but the main contribution of heat gain is the solarradiation heat gain.Solar radiation heat gain values varies every day with respect to the different position of the sun.In order to solve energy wastage problem in airconditioning system, the computation of the solar radiation heat gain is done. In this study the equations used are the ‘Clear-sky Solar Radiation’ as suggested by ASHRAE in book of fundamentals 2009. The equations are then being made acomputer model ofC++ computer programming by using Code::Blocks version 8.02 to calculate the solarradiation heat gain.The heat gain of every months are represented by the heat gain ontheir 21st day. The results are then being plotted into graphs to show the relationship between Irradiance, E and Total Solar Radiation Heat Gain, Q to a building. Lastly, the total solar radiation heat gain curves for twelve months are being plotted in anothergraphs for ease of analysis on how the sun position can actually affect the solarradiation heat gain.